STRATEGI BRAINSTORMING TERHADAP KETERAMPILAN BERPIKIR KREATIF - Lena Susianti; Muhammad Anwar (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This research was conducted to determine the effect of brainstorming strategies on students' creative thinking skills in workshop work subjects and technical drawing of class X students of Electronic Engineering at SMKN 1 Bukittinggi. The research design in this study is quasi-experimental. The instrument used was in the form of a matter of creative thinking skills tests that had been validated by an Expert, namely a lecturer majoring in Electronics Engineering. Validity test obtained the average value of validity of 0.85 which is in the valid category. Reliability test obtained Alpha Cronbach's value of 0.856 which is in the interpretation of the value of the pair very well. Because the questions are valid and reliable, the matter of creative thinking skills can be used. The results found the mean value in the experimental class (X TE1) 87.5 and the average value of the control class (X TE2) 74.0. After t-test, it was obtained that tcount> ttable so that Ha was accepted and Ho was rejected. It can be concluded that there is a significant influence on the application of brainstorming strategies to creative thinking skills.          Keywords: Creative Thinking Skills, Brainstorming Strategies, Validity, Reliability